2021
DOI: 10.1093/ehjdh/ztab018
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and repeatability of a smartphone-based 6-min walk test as a patient-centred outcome measure

Abstract: Background The 6-Mniute-Walk-Test (6MWT) is a validated proxy for frailty and a predictor of clinical outcomes, yet is not widely used due to implementation challenges. This comparative effectiveness study assesses the reliability and repeatability of a home-based 6MWT compared to in-clinic 6MWTs in patients with cardiovascular disease. Methods One hundred and ten (110) patients scheduled for cardiac or vascular surgery were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The traditional 6MWT is staff supervised within an unobstructed 30-m hallway 22 ; especially indoors, most patients will not be able to replicate this hallway at home. Others have reported different strategies for remote 6MWT including algorithms developed to estimate walk distance based on wearables 20,25 or smartphones 19,[25][26][27][28] ; global positioning system (GPS)-enabled devices can estimate walk distance outdoors, 19,29 and LaPatra et al 12 used remote observation. These different approaches were tested in a wide variety of individuals including healthy control subjects 27 and patients with strokes, 29 pulmonary hypertension, 12 peripheral vascular disease, 26 and coronary artery disease 26 ; the courses were also variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional 6MWT is staff supervised within an unobstructed 30-m hallway 22 ; especially indoors, most patients will not be able to replicate this hallway at home. Others have reported different strategies for remote 6MWT including algorithms developed to estimate walk distance based on wearables 20,25 or smartphones 19,[25][26][27][28] ; global positioning system (GPS)-enabled devices can estimate walk distance outdoors, 19,29 and LaPatra et al 12 used remote observation. These different approaches were tested in a wide variety of individuals including healthy control subjects 27 and patients with strokes, 29 pulmonary hypertension, 12 peripheral vascular disease, 26 and coronary artery disease 26 ; the courses were also variable.…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported different strategies for remote 6MWT including algorithms developed to estimate walk distance based on wearables 20,25 or smartphones 19,[25][26][27][28] ; global positioning system (GPS)-enabled devices can estimate walk distance outdoors, 19,29 and LaPatra et al 12 used remote observation. These different approaches were tested in a wide variety of individuals including healthy control subjects 27 and patients with strokes, 29 pulmonary hypertension, 12 peripheral vascular disease, 26 and coronary artery disease 26 ; the courses were also variable. All of the different methods showed high agreement between estimated and directly measured 6MWT distance, performed at about the same time.…”
Section: Discussionmentioning
confidence: 99%
“…The 6MWT is a functional capacity assessment method for patients with cardiopulmonary conditions usually performed in a pulmonary function laboratory. Mak et al [ 18 ] used iPhones and Apple Watches to measure the reliability of the 6MWT performed outside the laboratory. For patients performing an in-clinic 6MWT, the researchers noted an error between ground truth and phone-calculated steps ranging from 2.0% to 8.0% [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mak et al [ 18 ] used iPhones and Apple Watches to measure the reliability of the 6MWT performed outside the laboratory. For patients performing an in-clinic 6MWT, the researchers noted an error between ground truth and phone-calculated steps ranging from 2.0% to 8.0% [ 18 ]. Our study used the 6MWT as a surrogate marker of functional impairment following hospitalization.…”
Section: Methodsmentioning
confidence: 99%
“…Over the past decades, as a result of a noticeable growth in the eld of oncology rehabilitation and exercise, the use of the 6MWT has increased in this population although studies on its test-retest reliability are scarce [7]. In patients with cardiorespiratory diseases where the 6MWT has been most widely applied, the test-retest reliability was found to be excellent with intra-class correlation coe cients (ICC) ranging from 0.88 to 0.99 [8][9][10][11][12]. However, despite this high correlation, most studies have reported improvements in the distance covered during the second test, indicating the existence of a learning effect which has led to a recommendation of performing a re-test [9,13].…”
Section: Introductionmentioning
confidence: 99%